2018
DOI: 10.1210/jc.2018-00330
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, Placebo-Controlled Trial to Evaluate Effects of Eplerenone on Metabolic and Inflammatory Indices in HIV

Abstract: MR blockade may improve selected metabolic and inflammatory indices in HIV-infected individuals. Further studies are necessary to understand the clinical potential of MR antagonism in HIV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 28 publications
0
22
0
Order By: Relevance
“…The observations above would suggest that mineralocorticoid receptor blockade could be beneficial for HIV-induced Mets. However, a study of eplerenone showed improvement in some inflammatory markers but not in insulin resistance in HIV subjects with MetS [57].…”
Section: The Renin-angiotensin Systemmentioning
confidence: 95%
“…The observations above would suggest that mineralocorticoid receptor blockade could be beneficial for HIV-induced Mets. However, a study of eplerenone showed improvement in some inflammatory markers but not in insulin resistance in HIV subjects with MetS [57].…”
Section: The Renin-angiotensin Systemmentioning
confidence: 95%
“…A small open-label study evaluating the effect of MR antagonism in HIV reported increases in liver fat [ 26 ]. We recently performed a larger placebo-controlled randomized clinical trial evaluating MR antagonism in HIV and demonstrated no treatment effect on liver fat compared with placebo [ 11 ]. Because few data are available, our primary aim in the current study was to explore the fundamental relationship of aldosterone to liver fat in HIV.…”
Section: Discussionmentioning
confidence: 99%
“…Forty-six individuals between the ages of 30 and 65 years with a known history of HIV >5 years and ART use >12 months were recruited to participate in a longitudinal study investigating a novel strategy to block the RAAS in HIV [ 11 ]. In the current study, we used baseline data from the previously completed interventional study to report relationships among key metabolic variables, specifically related to liver fat and aldosterone.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased aldosterone signaling has been implicated in heart failure, diabetic cardiovascular injury including diabetic cardiomyopathy and may also play a role in the pathophysiology of insulin resistance 119 . Inhibition of aldosterone receptor signaling with eplerenone may reduce indices of inflammation and markers of insulin resistance in HIV infected subjects 120 . Thus, it would be of interest to determine metabolic and cardiovascular outcomes (including heart failure incidence) in high-risk subjects with diabetes treated with aldosterone receptor antagonists.…”
Section: Heart Failure Therapies and Their Effect On Glycemic Controlmentioning
confidence: 99%